Differential germination associated with facultative vivipary in Stenocereus thurberi (Cactaceae): climatic correlations in marginal populations in Sinaloa, Mexico - Casillas Álvarez, Pedro; Reyes Olivas, Alvaro; Sánchez-Soto, Bardo Heleodoro; García Moya, Edmundo; Lugo-García, Gabriel Antonio; Soto-Hernández, Ramón Marcos (Instituto de Ecología, A.C., 2018)
Background and Aims: Precocious (viviparous) seed germination in fruits of Stenocereus thurberi has been correlated with higher germination rate of the remaining seeds. This study compares the germination of five populations from Sinaloa, Mexico, to determine: 1) whether there is a pattern associated with precocious seed germination and, 2) how much the viviparous phenomenon accounts for germination compared to variation between fruits, individuals and populations of the cactus.Methods: The incidence of vivipary was recorded in 194 plants, and seeds were separated into four putative sources of variance: populations, reproductive categories (VV: viviparous, NV: non-viviparous), individuals within categories and fruits within individuals. The seed germination response in percentage (PGF), mean time (TMG), rate (VG), and synchrony of germination (SG) was evaluated under a randomized complete blocks scheme with three replicates, in experimental units of 25 seeds. Data were analyzed with hierarchical ANOVAs for a linear mixed model.Key results: Reproductive categories accounted for 5-11% of variance and showed significant differences in favor of viviparous phenotypes, with PGF of 35 vs 19% and 91 vs 72%, VG of 1.5 vs 0.5 and 7.9 vs 5.4 seeds/day, and SG of 0.3 vs 0.1, 0.7 vs 0.5 and 0.8 vs 0.6. Buenavista and Tosalibampo populations showed higher percentage, rate and synchrony of germination than the other populations (P<0.05, Student t-test).Conclusions: There is a seed germination pattern associated to vivipary in S. thurberi. The variance accounted by this condition depends on the environment in which seed maturation and germination occur. The seeds from viviparous phenotypes showed higher germination vigor than seeds from non-viviparous plants, revealing potential for seedling recruitment and population growth under drought and salinity stress.